KUE MARIJA (MADUSARI JAGUNG) SEBAGAI INOVASI MAKANAN TRADISIONAL SEHAT BERBASIS PANGAN LOKAL - Endang Mulyatiningsih, Nea Meiliandari (Prosiding Pendidikan Teknik Boga Busana, 2020)
Kue Marija (Madusari Corn) is a product developed using 100% corn flour and sweet corn. The product of the research was made to produce a new development recipe and to find out the level of preference or acceptance of the community. This study uses the Research and Development (R & D) method with a 4-D model (define, design, develop and dissemination) and uses the T-test to find out the panelist's acceptability. From the results of a limited panelist test of marija cake products viewed in terms of color, aroma, taste and overall has a P value of more than 0.05 which means it is not significantly different from the reference product. While the texture has a P value of less than 0.05, which means that it is significantly different from the reference product. Judging from the results of the untrained panelist testing at the exhibition, the average results of 3.8 were obtained on all observations. This shows that marija cake products are very popular and acceptable to the public. From the proximate test that has been done shows that Kue Marija (Madusari Corn) contains high carbohydrates of 44.22 grams and has an energy content of 252.6 cal / gram. Therefore, this Marija cake product can be used as a healthy traditional food based on local food which is filling and healthy because it is made from 100% corn flour and sweet corn. Keywords: Corn Flour, Sweet Corn, Kue Marija, Development, Panelists